Sexual dysfunction in drug- naïve first episode nonaffective psychosis patients. Relationship with prolactin and psychotic symptoms. Gender differences. (July 2020) - Del Cacho, N.; Vila - Badia, R.; Butjosa, A.; Cuadras, D.; Rubio - Abadal, E.; Rodriguez - Montes, M.J.; Muñoz- Samons, D.; Dolz, M.; Usall, J.; ,
Highlights: We found evidence for better sexual functioning in controls than in patients with first episode psychosis. Disorganized symptomatology could be a relevant factor in sexual functioning of first episode psychosis. These study is relevant in increasing the knowledge on sexual dysfunction in first episode psychosis. Abstract: Background: Our aim is to examine differences in sexual functioning (SF) between patients with drug-naïve first episode psychosis (FEP) and healthy controls (HC). We will also examine correlations between prolactin levels, testosterone levels and psychotic symptomatology with SF from a gender perspective. Methods: Cross-sectional study. We included 68 FEP patients and 50 HC. A blood sample was extracted. We used the Positive and Negative Syndrome Scale to assess symptom severity, using the five factor structure according to Emsley. The Changes in Sexual Function Questionnaire (CSFQ) was administered. Results: We found significantly better SF in HC than in patients (in CSFQ total score ( p  = 0.032) and in CSFQ Desire ( p  = 0.032)). A significant correlation between prolactin or testosterone and SF was not observed. We found a negative significant correlation between the disorganised subscale of the EMSLEY and total CSFQ ( p  = 0.027; r  = −0.329), CSFQ Desire ( p  = 0.028; r  = −0.329) and CSFQ Arousal ( p  = 0.026; r  = −0.332) in the patient sample. In a regression model, we found sex ( p  = 0.003) and disorganized symptoms ( p  = 0.034) as significant predictors. Conclusions: We found evidence for better SF in HC than in FEP patients. We could not confirm an association between prolactin or testosterone and SF. Disorganized symptomatology could be a relevant factor in SF.